Forest types for biodiversity assessment at regional level: the case study of Sicily (Italy) - Cullotta, Sebastiano; Marchetti, Marco (European Journal of Forest Research, 2007)
Within Europe the question of plant coenosis is attracting growing interest. The quality and quantity of collected information on forest resources at a global level largely depends on the capacity to collect and analyse data at national and sub-national scale in a way compatible with those at global or continental levels. In Italy the acceptance of all the international agreements and protocols on the protection of the environment and management of natural resources, requires a standardization of collected information and statistics, with the aim to produce homogeneous and integrative data at global level. This need is reﬂected in the following points: (1) the adoption of a classiﬁcation system of land use and forest cover compatible with international hierarchical systems and deﬁnitions; (2) the identiﬁcation of standard procedures in data collection and data elaboration. To classify natural resources and, in this case study, forest resources, implies to order natural and semi natural coenosis, forest and pre-forest communities, in a systematic way, according to the applied variables and to the scale detail. The solution proposed in this case study is organised according to forest management, through the adoption of the habitat approach, describing forest and pre-forest types in a synoptic way and performing a system of nomenclature in agreement with the international standards initiatives. In this way, the characterization of forest types at community level is related to the environmental planning for the protection of biodiversity
Keywords: Ecological stratiﬁcation; Forest biodiversity; Forest community; forest type; Hierarchical system; Stand-management unit

Forest types for biodiversity assessment at regional level: the case study of Sicily (Italy) - Cullotta, Sebastiano; Marchetti, Marco (European Journal of Forest Research, 2007)
Within Europe the question of plant coenosis is attracting growing interest. The quality and quantity of collected information on forest resources at a global level largely depends on the capacity to collect and analyse data at national and sub-national scale in a way compatible with those at global or continental levels. In Italy the acceptance of all the international agreements and protocols on the protection of the environment and management of natural resources, requires a standardization of collected information and statistics, with the aim to produce homogeneous and integrative data at global level. This need is reﬂected in the following points: (1) the adoption of a classiﬁcation system of land use and forest cover compatible with international hierarchical systems and deﬁnitions; (2) the identiﬁcation of standard procedures in data collection and data elaboration. To classify natural resources and, in this case study, forest resources, implies to order natural and semi natural coenosis, forest and pre-forest communities, in a systematic way, according to the applied variables and to the scale detail. The solution proposed in this case study is organised according to forest management, through the adoption of the habitat approach, describing forest and pre-forest types in a synoptic way and performing a system of nomenclature in agreement with the international standards initiatives. In this way, the characterization of forest types at community level is related to the environmental planning for the protection of biodiversity
Keywords: Ecological stratiﬁcation; Forest biodiversity; Forest community; forest type; Hierarchical system; Stand-management unit